The Aggregate and Distributional Effects of Financial Globalization : Evidence from Macro and Sectoral Data - Furceri, Davide (IMF Working Papers; Working Paper ;, 2018)
We take a fresh look at the aggregate and distributional effects of policies to liberalize international capital flows-financial globalization. Both country- and industry-level results suggest that such policies have led on average to limited output gains while contributing to significant increases in inequality-that is, they pose an equity-efficiency trade-off. Behind this average lies considerable heterogeneity in effects depending on country characteristics. Liberalization increases output in countries with high financial depth and those that avoid financial crises, while distributional effects are more pronounced in countries with low financial depth and inclusion and where liberalization is followed by a crisis. Difference-indifference estimates using sectoral data suggest that liberalization episodes reduce the share of labor income, particularly for industries with higher external financial dependence, those with a higher natural propensity to use layoffs to adjust to idiosyncratic shocks, and those with a higher elasticity of substitution between capital and labor. The sectoral results underpin a causal interpretation of the findings using macro data.